Theory of cost and production functions - Shephard, Ronald William (Princeton, N.J.: Princeton University Press, 1970)
This book offers a unified, comprehensive treatment of cost and revenue functions for technologies defined by mappings of output vectors representing the unconstrained technical possibilities of production
Includes index
osc 26/03/2019
Loans
Keywords: Cost; Value; Economics, Mathematical